Foul play [videorecording (DVD)] - Higgins, Colin, 1941-1988; Hawn, Goldie; Chase, Chevy; Meredith, Burgess, 1907-1997 (Paramount, 2004)
A librarian is propelled into a world of chase scenes and bizarre attempts on her life after she hears a secret code.